Donor understandings of blood and the body in relation to more frequent donation. Issue 4 (9th February 2018) - Lynch, R.; Cohn, S.
Abstract : Background and objectives: The INTERVAL trial aimed to find the optimum frequency of blood donation to enhance blood supplies and maintain donor health. This not only requires biological knowledge, but also an appreciation of donor perspectives, and how their experiences and beliefs might be central if any changes are ever to be made. To address this, trial participants were interviewed about their ideas of blood and the body in relation to their experiences of increased donation frequency. Materials and methods: Thirty in depth face‐to‐face interviews conducted with blood donors participating in the trial. Results: Three key themes emerged: ideas about how blood and iron reserves are replenished, and what people did to facilitate this; beliefs about physiological differences relating to age and gender; and practical issues that affected the experience of donation. Overall, participants interviewed welcomed more frequent donation, despite a range of pragmatic concerns. Conclusion: Despite some practical obstacles, increased donation frequency aligned with participant's ideas about bodily replenishment, the value of donation, and their identity as enduring blood donors. They therefore supported the idea of increasing frequency of donation, independently of the biomedical evidence from the trial itself.